Sulfur dioxide in the tropical marine boundary layer: dry deposition and heterogeneous oxidation observed during the Pacific Atmospheric Sulfur Experiment - Faloona, Ian; Conley, Stephen A; Blomquist, Byron; Clarke, Antony D; Kapustin, Vladimir; Howell, Steven; Lenschow, Don H; Bandy, Alan R (Journal of atmospheric chemistry, 2009)
Research flights with the National Center for Atmospheric Research (NCAR) C-130 airborne laboratory were conducted over the equatorial ocean during the Pacific Atmospheric Sulfur Experiment (PASE). The focused, repetitive flight plans provided a unique opportunity to explore the principal pathways of sulfur processing in remote marine environments in close detail. Fast airborne measurements of SO₂ using the Drexel University APIMS (Atmospheric Pressure Ionization Mass Spectrometer) instrument further provided unprecedented insight into the complete budget of this important sulfur gas. In general, turbulent mixing in the marine boundary layer (MBL) continuously depletes SO₂ due to the shallow convection of the tropical trade wind regime by venting the gas into the buffer layer (BuL) above. However, on nearly one-third of the flights a net import of SO₂ into the MBL from the BuL was observed. Concurrent measurements of the DMS budget allowed for a heterogeneous S(IV) oxidation rate to be inferred from the SO₂ budget residual. The average heterogeneous loss rate was found to be 0.05 h⁻¹, which taken in conjunction with the observed aerosol surface area distributions and O₃ levels indicates that the supermicron aerosols maintain a near neutral pH. The average dry deposition velocity of SO₂ was found to be 0.4 cm s⁻¹, about 30% lower than predicted by standard parameterizations. The yield of SO₂ from DMS oxidation was found to be near unity. The mission averages indicate that approximately 57% of the SO₂ in the MBL is lost to aerosols, 27% is subject to dry deposition, 7% is mixed into the BuL, and 10% is oxidized by OH.